Pembentukan Karakter Islami pada Siswa di SMP Swasta Se-Kota Binjai - Muhandis Alfalah; Yusnaili Budianti; Azizah Hanum OK (Cetta: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to analyze the methods, the inhibiting factors  in the process of forming students'  Islamic character and the solutions used as a reference  in the formation of students'  Islamic character  in private junior high schools  in Binjai City. The method of this research s to use qualitative research methods  in order to reveal  in depth data and facts about the formation of the  Islamic character of students  in private junior high schools throughout the City of Binjai. Data collection techniques using  interviews, observation, and document review. Then the data were analyzed by data reduction, data presentation, and conclusion. The results of this study are that the formation of the  Islamic character of students s taken from two schools,  inamely Al Kaffah Binjai  integrated  Islamic Middle School and Binjai PABA Middle School, each school has a method of forming students'  Islamic character. However,  in essence the methods used by each school are closely related to the formation of the  Islamic character of students. The methods used are giving advice, getting used to good morals, exemplary, Targhib and Tarhib, stories, and parables. in carrying out these methods,  inhibiting factors were also found  in the formation of  Islamic character of students.  inhibiting factors that occur due to the lack of religious education  in the family, unfavorable environment, lack of awareness of students to carry out conditions related to religion and rampant  information from social media. The solution to these  inhibiting factors s to prepare professional educators, create a good environment, complete  infrastructure, and create  intra-curricular and extra-curricular programs as supports  in the formation of  Islamic character of students at Al Kaffah Binjai  integrated  Islamic Middle School and Binjai PABA Middle School.